Loading and distribution of the 2000 high frequency words in Malaysian English language textbooks for Form 1 to Form 5 - Mukundan, Jayakaran; Aziz, Anealka (Universiti Putra Malaysia Press, 2009)
Textbooks are important tools used by teachers in teaching. Today, thanks to corpus-based research and the use of concordance software to analyze language, entire textbooks can be scanned to form what we call a corpus of the language of English language textbooks. Concordance software is used to perform automated and semi-automated analyses in terms of loading and distribution of words in textbooks. In this study, the researchers studied patterns of loading, distribution and repetition, and investigated cases of words missing in books, all based on the 2000 high frequency word list. Results of the study reveal that while most of the 2000 high frequency words (93.1%) are used in the secondary school textbooks, repetition and recycling are not efficient. The research also revealed that there are 139 (6.9%) words in the 2000 high frequency word list which are not used at all in Malaysian English language textbooks. The results also caution material developers that high coverage of the 2000 high frequency words does not ensure effective learning, especially when the words are poorly distributed within and across textbooks.